PENGADAAN BIMBINGAN BELAJAR DI MASA PANDEMI DAN PEMBAGIAN MASKER SEBAGAI EDUKASI PROTOKOL KESEHATAN PENCEGAHAN COVID 19 DI MASYARAKAT - Andi Alif Tunru Andi Alif; Rahmat Ilahi; Samsul Adianto; Tiana Anugrah Salsabilla (Jurnal Pengabdian Kreativitas Pendidikan Mahakam (JPKPM), 2022)
The COVID-19 pandemic has affected many fields, one of which is the field of education. Education is one of the most affected by the COVID-19 pandemic. Education staff and the government are trying their best so that education continues to run smoothly and optimally even during the current pandemic. During the COVID-19 pandemic, the government carried out online or remote teaching and learning activities. Online or distance learning is an effort to keep the learning going well even though using different systems or different learning methods. The provision of tutoring is something that must be done so that students can still achieve the expected competencies, not only that but complying with Health protocols also needs to continue to be carried out by providing masks so that the virus can be prevented from spreading and schools can meet face to face